2011
DOI: 10.1371/journal.pone.0025467
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel Deficiency Increases Caspase-4 Expression and Leads to ER Stress and Necrosis in EBV-Transformed Cells

Abstract: LMP1-mediated activation of nuclear factor of kappaB (NF-κB) is critical for the ligand independent proliferation and cell survival of in vitro EBV-transformed lymphoblastoid cell lines (LCLs). Previous experiments revealed that a majority of LMP1-dependent responses are regulated by NF-κB. However, the extent that individual NF-κB family members are required for these responses, in particular, c-Rel, whose expression is restricted to mature hematopoietic cells, remains unclear. Here we report that low c-Rel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…During EBV infection, REL and STAT3 have a potent effect on cell growth and in lymphomagenesis [26]. On the contrary, REL deficiency leads to decreased proliferation, decreased survival of EBV transformed cells and could even lead to their necrotic death [27]. In HTLV infection, REL proteins are involved in the canonical NF-κB pathway, which induces the transcription of anti-apoptotic BCL2A1 and BCL2L1 [28].…”
Section: Discussionmentioning
confidence: 99%
“…During EBV infection, REL and STAT3 have a potent effect on cell growth and in lymphomagenesis [26]. On the contrary, REL deficiency leads to decreased proliferation, decreased survival of EBV transformed cells and could even lead to their necrotic death [27]. In HTLV infection, REL proteins are involved in the canonical NF-κB pathway, which induces the transcription of anti-apoptotic BCL2A1 and BCL2L1 [28].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also found that caspase-4 expression is NF-κB p65-dependent, as evidenced by increased caspase-4 expression in p65-overexpressing cells. Not uniquely, another NF-κB isoform, c-Rel, was also found to be associated with caspase-4 expression in EBV-transformed cells [ 40 ]. However, the authors demonstrated that c-Rel negatively modulates the expression of caspase-4.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the viral LMP1 protein from EBV associates with the lipid raft microdomains to activate NF-κB, and it also induces autophagy 33,60 . However it is currently not clear if the lipid raft microdomain is involved in the LMP1-mediated autophagic process.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that Tax-deregulated autophagy was involved in the lipid raft recruitment of the autophagic molecular complex containing Beclin1 and Bif-1 and that this action was also dependent on the activity of IκB kinases. Similarly, the viral LMP1 protein from EBV associates with the lipid raft microdomains to activate NF-κB, and it also induces autophagy 33 , 60 . However it is currently not clear if the lipid raft microdomain is involved in the LMP1-mediated autophagic process.…”
Section: Discussionmentioning
confidence: 99%